OUTCOME OF INVASIVE SECOND LINE MANAGEMENT OF PRIMARY POSTPATUM HEAMORRHAGE - Zahoor, Farnaz; Jabeen, Sadaqat (Journal of Postgraduate Medical Institute, 2019)
Objective: To find out the outcome of surgical treatment for primary postpartum hemorrhage (PPH). Methodology: It was a descriptive case series study conducted in Department of Gynecology and Obstetrics Lady Reading Hospital Peshawar from January to December 2017. Total 292 patients with primary PPH were enrolled in which 53 women had failed to improve with medical management or required invasive treatment in first instance. Those 53 patients were managed accordingly either with uterine compression suture, pelvic vessel ligation or hysterectomy. Their outcomes were measured as rate of use of specific procedure, failure of invasive therapy and reverting from one to another procedure. Data were entered and analyzed with SPSS version 17 for descriptive statistics. Results: Postpartum hemorrhage was treated using second line surgical procedures in 53 patients out of 292 cases of PPH. The primary cause of PPH in these patients who underwent surgery was uterine atony in half of the patients followed by other pathologies. Most patients received conservative treatment including uterotonic therapy before undergoing 2nd line management of invasive therapy. Majority (32 patients underwent subtotal abdominal hysterectomy (STAH). Seventeen patients had b lynch uterine compression suture, 3 patients had repair of ruptured uterus while 1% had uterine artery ligation (UAL). Various morbidities were seen in these patients with massive hemorrhage, ICU admission, anemia, renal failure and septicemia. Conclusion: Invasive therapy in the form of surgery including hysterectomy was effective in controlling bleeding in life threatening situations when first-line treatment fails.